2015
DOI: 10.1002/cbf.3094
|View full text |Cite
|
Sign up to set email alerts
|

The proteins (12 and 15 kDa) isolated from heat‐killed Lactobacillus plantarum L67 induces apoptosis in HT‐29 cells

Abstract: A number of scientific studies have revealed that Lactobacillus strains have beneficial bioactivities in the gastrointestinal tract. In this study, the production of intracellular reactive oxygen species (ROS) and the amounts of intracellular calcium, protein kinase C activity, cytochrome c, Bid, Bcl-2, Bax and the apoptosis-mediated proteins [caspase-8, caspase-3 and poly ADP ribose polymerase (PARP)] were evaluated to understand the induction of programmed cell death in HT-29 cells by Lactobacillus plantarum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 39 publications
2
16
0
Order By: Relevance
“…Surface receptors for extrinsic apoptosis, such as TNF-α, are produced by immune system cells and Fas, which are able to activate the cytosolic protease, caspase-8. Caspase-8 activates caspase-3, caspase-6, and caspase-7 that leading to apoptosis induction (32). In this way, Kim et al revealed that B. adolescentis potentiated the production of TNF-α, as a cytokine that induces apoptosis, and their results supported our results (31).…”
Section: Discussionsupporting
confidence: 88%
“…Surface receptors for extrinsic apoptosis, such as TNF-α, are produced by immune system cells and Fas, which are able to activate the cytosolic protease, caspase-8. Caspase-8 activates caspase-3, caspase-6, and caspase-7 that leading to apoptosis induction (32). In this way, Kim et al revealed that B. adolescentis potentiated the production of TNF-α, as a cytokine that induces apoptosis, and their results supported our results (31).…”
Section: Discussionsupporting
confidence: 88%
“…Surface receptors for extrinsic apoptosis, such as TNF-α, are produced by immune system cells and Fas, which are able to activate the cytosolic protease and caspase-8. Then, the caspase-8 activates caspase-3, caspase-6, and caspase-7 that leading to extrinsic apoptosis induction (38). In this way, Kim et al revealed that B. adolescentis potentiated the production of TNF-α, as a cytokine that induces apoptosis, and their results supported our results about the induction of apoptosis by this bacteria species (36).…”
Section: Discussionsupporting
confidence: 86%
“…Surface receptors for extrinsic apoptosis, such as TNF-α, are produced by immune system cells and Fas, which are able to activate the cytosolic protease and caspase-8. Then, the caspase-8 activates caspase-3, caspase-6, and caspase-7 that leading to extrinsic apoptosis induction [ 38 ]. In this way, Kim et al revealed that B. adolescentis enhances the production of TNF-α, as a cytokine that induces apoptosis, and their results supported our findings about the induction of apoptosis by this bacteria species[ 36 ].…”
Section: Discussionmentioning
confidence: 99%